Research on professional responsibility and ethics in accounting. vol. 25 - Shawver, Tara J. (Emerald Publishing Limited, 2023)
This 25th edition of Research on Professional Responsibility and Ethics in Accounting includes articles from a diverse group of expert authors. Subjects covered explore many aspects across professional responsibility and ethics in accounting, including balancing values vs profits, whistleblowing, earnings management, ethical financial reporting, and moral identity.
Keywords: Accounting -- Moral and ethical aspects.; Accountants -- Professional ethics.; Business & Economics -- Accounting -- General.; Accounting.; elektronické knihy; electronic books